Effects of medium and culture conditions on folate production by Streptococcus thermophilus BAA-250. - Mousavi, Seyed Sadegh; Moeini, Hassan; Mohamad, Rosfarizan; Dinarvand, Mojdeh; Ariff, Arbakariya; Foo, Hooi Ling; Abdul Rahim, Raha (2013)
The present study was conducted to investigate the effects of culture conditions on folate production by Streptococcus thermophilus BAA-250. Lactose (3g/L) and yeast extract (20g/L) were found to be the more suitable carbon and nitrogen sources for folate production by S. thermophilus BAA-250. para-aminobenzoic acid (pABA) higher than 1 µM had no significant effect on folate biosynthesis. The optimum pH for folate production was shown to be 7.0 with a folate yield and productivity of 54.53 (µg/L) and 2.27 (µg/L.h), respectively. Optimum folate production obtained in the presence of lactose and yeast extract in a controlled pH of 7 during batch fermentation in bioreactor. Kinetic studies indicated that folate production by S. thermophilus is growth-associated process.